Transparent conductive film and preparation method and application thereof
By forming a hydrophobic layer on the surface of the substrate and opening a connecting groove, the conductive material automatically shrinks to form a grid-like conductive layer, the problem that existing transparent conductive films are difficult to form a grid-like conductive layer is solved, and efficient conductivity and optical Performance, suitable for a variety of electronic devices.
Patent Information
- Application Number
- CN202411215271.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
The existing transparent conductive film is difficult to form a grid-like conductive layer, which affects its application in electronic display devices, solar cells and other fields.
A hydrophobic layer is formed on the surface of the substrate, and a communicating groove is opened on the surface of the hydrophobic layer. The conductive material automatically shrinks and accumulates in the groove after sintering to form a grid-shaped conductive layer.
The grid-like structure of the transparent conductive film is realized, and its conductivity and optical properties are improved. It is suitable for applications such as antennas, touch electrodes, electromagnetic shielding films, heating films, electronic display devices, solar cells, and touch screens.
Smart Images

Figure CN119132699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and in particular to a transparent conductive film and a preparation method and application thereof. Background Art
[0002] As an important emerging material, transparent conductive film has broad application prospects in the fields of electronic display devices, solar cells, touch screens, etc. However, it is difficult for existing transparent conductive films to form a grid-shaped conductive layer.
[0003] In view of this, it is necessary to improve the existing transparent conductive film and its preparation method and application to solve the above problems. Summary of the invention
[0004] The object of the present invention is to provide a transparent conductive film and a preparation method and application thereof, so as to solve at least one of the above-mentioned technical problems.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0006] A transparent conductive film, comprising:
[0007] A substrate, the substrate comprising a substrate, a hydrophobic layer located on at least one surface of the substrate, and grooves recessed from the surface of the hydrophobic layer toward the side where the substrate is located, wherein at least some of the grooves are interconnected;
[0008] The conductive layer is located in the groove.
[0009] In an optional embodiment, the hydrophobic layer is selected from a combination of at least one or more of a nano-silicon dioxide film layer, a polydimethylsiloxane film layer, or a polytetrafluoroethylene film layer.
[0010] In an optional embodiment, the hydrophobic layer has a thickness of 1 μm to 5 μm.
[0011] In an optional embodiment, the surface roughness of the hydrophobic layer is 1 nm to 200 nm.
[0012] In an optional embodiment, the surface contact angle of the hydrophobic layer surface is not less than 90° and not more than 170°.
[0013] In an optional embodiment, the groove includes a plurality of interconnected sub-grooves, and the plurality of sub-grooves extend in at least two directions; and the included angle of the mutually intersecting and interconnected sub-grooves is 40° to 140°.
[0014] In an optional embodiment, the groove is in a grid shape as a whole, and the grid pattern is a polygon or an irregular shape. The polygon is a triangle, a quadrilateral, a pentagon, or a hexagon, and the sides of the polygon are straight lines or arcs.
[0015] In an optional embodiment, the groove runs through the hydrophobic layer.
[0016] In an optional embodiment, the groove penetrates the hydrophobic layer, and a portion of the groove is recessed inward from the surface of the substrate.
[0017] In an optional implementation, the depth of the groove is 1 μm to 30 μm.
[0018] In an optional implementation, the width of the groove is 3 μm to 20 μm, and the distance between adjacent grooves is 100 μm to 1000 μm.
[0019] In an optional embodiment, the conductive layer is a conductive network formed by a conductive material coated in the groove, and the conductive layer completely fills the groove; or the conductive layer is higher than the groove in the thickness direction of the substrate.
[0020] A method for preparing a transparent conductive film comprises the following steps:
[0021] forming a hydrophobic layer on at least one surface of a substrate;
[0022] Grooves are formed on the surface of the hydrophobic layer, and at least some of the grooves are interconnected;
[0023] A conductive material is coated in the groove and sintered to form a conductive layer.
[0024] In an optional embodiment, the hydrophobic material is coated on the surface of the substrate by blade coating, spin coating, spray coating, slit coating, or inkjet printing, and then sintered and cured at 80° C. to 160° C.
[0025] In an optional embodiment, the hydrophobic material is selected from a combination of at least one or more of a nano-silicon dioxide film layer, a polydimethylsiloxane film layer, or a polytetrafluoroethylene film layer.
[0026] In an optional implementation, the groove is formed by laser etching, and the laser power is 1W to 30W.
[0027] In an optional embodiment, the conductive material is coated on the entire surface of the substrate, and the conductive material shrinks into the groove on the surface and extends along the groove.
[0028] In an alternative embodiment, the conductive material is applied only in the grooves.
[0029] In an optional embodiment, the amount of the conductive material in a wet film state is 1.2 to 3 times the volume of the groove.
[0030] In an optional embodiment, the amount of the conductive material in a dry film state is 1 to 1.5 times the volume of the groove.
[0031] In an optional embodiment, the method for preparing the transparent conductive film further comprises the step of forming a black conductive coating on the surface of the conductive layer.
[0032] The transparent conductive film is used in antennas, touch electrodes, electromagnetic shielding films, heating films, electronic display devices, solar cells, and touch screens.
[0033] A transparent conductive film prepared by the preparation method is used in antennas, touch electrodes, electromagnetic shielding films, heating films, electronic display devices, solar cells and touch screens.
[0034] The beneficial effects of the present invention are as follows: the transparent conductive film of the present invention, by arranging the hydrophobic layer on the surface of the substrate, makes the surface of the substrate have low surface energy, the conductive material in the area outside the groove is in the shape of water droplets rather than a wet state, and will not spread out, thereby automatically shrinking and finally gathering in the groove to form a conductive grid, and can form a grid-like conductive layer that fills the entire groove or even is higher than the groove. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a schematic diagram of a transparent conductive film according to one embodiment of the present invention;
[0036] Figure 2 is a schematic diagram of a transparent conductive film according to another embodiment of the present invention;
[0037] Figure 3 is a schematic diagram of a transparent conductive film before and after sintering according to an embodiment of the present invention;
[0038] Figure 4 is a schematic diagram of a transparent conductive film before and after sintering according to an embodiment of the present invention;
[0039] Figure 5 The present invention is a flow chart of a method for preparing a transparent conductive film according to an embodiment of the present invention.
[0040] Among them, 100 is a transparent conductive film, 1 is a substrate, 11 is a base material, 12 is a hydrophobic layer, 13 is a groove, and 2 is a conductive layer. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below in conjunction with specific embodiments.
[0042] Please refer to Figure 1 to Figure 4 Combined with Figure 5As shown, a transparent conductive film 100 according to an embodiment of the present invention comprises a substrate 1 and a conductive layer 2 located on at least one surface of the substrate 1 .
[0043] The substrate 1 is a basic supporting layer of the transparent conductive film 100 , and includes a base material 11 , a hydrophobic layer 12 located on at least one surface of the base material 11 , and a groove 13 sunken from the surface of the hydrophobic layer 12 .
[0044] The substrate 11 is a transparent film or sheet. The substrate 11 is selected from PET, PI, glass, PCV, PC, or PMMA. The thickness of the substrate 11 is 0.03 mm to 30 mm.
[0045] Specifically, when the substrate 11 is a film, it is selected from PET or PI, etc., and the thickness of the film is 0.03mm to 0.5mm. The thin plate is a thin plate selected from glass, PCV, PC, or PMMA, and the thickness of the thin plate is 0.5mm to 30mm.
[0046] The present invention arranges the hydrophobic layer 12 on the surface of the substrate 11, and the groove 13 is surrounded by the hydrophobic layer 12, so that the non-groove area (the area outside the groove 13) on the surface of the substrate 1 has a low surface energy, and the conductive material in the non-groove area is in a water droplet state rather than a wet state, and will not spread out, thereby automatically shrinking and finally gathering in the groove 13 to form a conductive grid.
[0047] In the present invention, the hydrophobic layer 12 is selected from a combination of at least one or more of a nano-silicon dioxide film layer, a polydimethylsiloxane film layer, or a polytetrafluoroethylene film layer. These materials have stable chemical properties, can maintain good hydrophobic properties under various environments, and are transparent films within a micrometer-level thickness range, without affecting the optical properties of the transparent conductive film.
[0048] The surface of the hydrophobic layer 12 has a micro-nano structure, which increases the roughness of the surface of the hydrophobic layer 12, further enhances the hydrophobicity, and allows the hydrophilic material to form a more stable contact angle on its surface. In one embodiment, the roughness of the surface of the hydrophobic layer 12 is 1nm to 200nm.
[0049] The surface contact angle of the hydrophobic layer 12 is not less than 90°. The larger the surface contact angle, the more conducive it is for the conductive material to gather in the groove 13. Preferably, it is not less than 120°, or not less than 130°, or not less than 140°, or not less than 150°. The conductive material spreads on the surface instantly, shrinks into the groove 13 immediately, and extends along the groove 13. Considering that the conductive material is not easy to be coated on the surface of the substrate 1 if the surface contact angle is too large, the surface contact angle in the present invention is not greater than 170°.
[0050] The thickness of the hydrophobic layer 12 is 1 μm to 5 μm, so as to ensure that a complete and continuous hydrophobic film layer is formed on the surface of the substrate 11 .
[0051] The grooves 13 are formed from the surface of the hydrophobic layer 12 toward the side where the substrate 11 is located, and are used to accommodate conductive materials to form a grid-shaped conductive layer 2 .
[0052] In one embodiment, the depth of the groove 13 is 1 μm to 30 μm. If the groove 13 is too shallow, the conductive material will easily overflow the groove 13; if the groove 13 is too deep, the process is difficult to implement, the width will increase, and the amount of conductive material used will be too high.
[0053] In one embodiment, the depth of the groove 13 is set to penetrate the hydrophobic layer 12, and the bottom of the groove 13 is the substrate 11, that is, the substrate 11 is exposed outward from the groove 13. Compared with the hydrophobic layer 12, the substrate 11 has a high hydrophilicity, which is conducive to the extension of the conductive material in the groove 13.
[0054] In another embodiment, the depth of the groove 13 is greater than the depth of the hydrophobic layer 12, that is, the groove 13 penetrates the hydrophobic layer 12, and a portion of the groove 13 is recessed inward from the surface of the substrate 11, that is, the groove 13 is opened on the substrate 11. The hydrophilic surface area at the bottom of the groove 13 is increased, which is more conducive to the spreading of the conductive material in the groove 13.
[0055] In addition, the width of the groove 13 is 3 μm to 20 μm. If the groove 13 is too narrow, it is difficult to realize in the process, the resistance is high, and the conductivity is poor; if the groove 13 is too wide, the optical properties of the conductive film, such as transparency, will be affected.
[0056] In a specific embodiment, the distance between adjacent grooves 13 is 100 μm to 1000 μm.
[0057] In addition, at least some of the grooves 13 are interconnected, so that the conductive layer 2 is in a grid shape with a predetermined pattern. Specifically, the interconnection mode of the grooves 13 is determined by the structural design and purpose of the transparent conductive film 100.
[0058] In one embodiment, all the grooves 13 on the entire substrate 1 are interconnected, so that the conductive material forms a conductive network covering the entire surface.
[0059] In another embodiment, the grooves 13 in the local area are interconnected to form a conductive area; the grooves 13 in other local areas are discontinuous, that is, there are multiple breakpoints in the extension direction of the grooves 13 that interrupt the connection of the grooves 13, forming a non-conductive area. Overall, the configuration of the grooves 13 in the conductive area and the non-conductive area is basically the same, so that the two areas have highly similar or highly consistent optical and visual effects.
[0060] The groove 13 includes a plurality of interconnected sub-grooves, and the plurality of sub-grooves extend in at least two directions. The extending directions of the mutually intersecting and interconnected sub-grooves are not limited, and the included angle between the two is a predetermined angle, which is 40° to 140°.
[0061] According to the conductive pattern design of the applied product, the groove 13 is in a grid shape as a whole. The grid pattern is a polygon or an irregular shape, the polygon is a triangle, a quadrilateral, a pentagon, or a hexagon, and the sides of the polygon are straight lines or arcs.
[0062] The conductive layer 2 is located in the groove 13, and specifically, the conductive material is coated in the groove 13 and sintered to form a grid-like conductive network. Figure 1 , Figure 2 As shown, the conductive layer 2 fills the groove 13. Figure 3 , Figure 4 As shown, the conductive layer 2 is higher than the groove 13 in the thickness direction of the substrate 1 , that is, the conductive layer 2 protrudes from the groove 13 .
[0063] According to the mass ratio, the conductive material includes:
[0064] Nano conductive materials, 50% to 85%;
[0065] Waterborne polyurethane resin, 5% to 15%;
[0066] Water-based epoxy resin, 2% to 15%;
[0067] Water-based acrylic resin, 5% to 20%;
[0068] Dispersant, 0.1-2%;
[0069] Curing agent, 0.1~2%.
[0070] The nano-conductive material mainly plays the role of conducting electricity, which is not less than 70%. The nano-conductive material is selected from nano-non-metallic materials or nano-metallic materials.
[0071] The nano non-metallic material is selected from at least one or more combinations of carbon nanotubes or graphene.
[0072] The metal in the nano metal material is at least one metal selected from gold or its alloy, silver or its alloy, copper or its alloy, iron or its alloy, nickel or its alloy.
[0073] The form of the nanometal material is selected from at least one or more combinations of nanometal powder or nanometal wire. The nanometal powder is selected from at least one or more combinations of flaky powder or spherical powder. There are many overlapping points between the materials, which can ensure the conductive performance. The nanometal wire has a large wire diameter ratio (ratio of length to diameter), which can also ensure good conductive performance and improve the overall flexibility of the transparent conductive film 100.
[0074] Preferably, the particle size of the nano metal powder is not greater than 30% of the width of the groove 13 , so that the nano metal in the conductive material forms an effective overlap, thereby ensuring the conductive performance of the conductive layer 2 .
[0075] In a specific embodiment, the particle size of the nano metal powder is 0.5 μm to 6 μm, preferably 500 nm to 800 nm.
[0076] The metal and state of the above-mentioned nano-metal materials can be arbitrarily matched. For example, the nano-metal powder includes at least one or more combinations of nano-silver powder, nano-copper powder, and nano-silver-coated copper powder; the nano-metal silver can include one or more combinations of nano-silver powder and nano-silver wire.
[0077] Waterborne polyurethane resin, waterborne epoxy resin and waterborne acrylic resin are the main bodies of the conductive materials, which combine the nano-conductive materials together and make the conductive materials have a certain hydrophilicity.
[0078] The dispersant is used to maintain the dispersion effect of the nano conductive material in the entire conductive material to prevent the nano conductive material from agglomerating. In the present invention, the dispersant is selected from one or more of the group consisting of phenolic resin, alkylamine, aromatic ether, alkanol, and epoxy resin.
[0079] The curing agent is selected from one or more combinations of hexamethylenediamine, epoxy resin, and polyisocyanate to promote the curing of the conductive material. The curing temperature is 80° C. to 160° C.
[0080] Based on the above design, the transparent conductive film 100 of the present invention has a square resistance of no more than 15Ω / sq and a light transmittance of no less than 80%, and has both good conductive properties and optical properties.
[0081] Furthermore, the transparent conductive film 100 further includes a dark conductive coating on the conductive layer 2 to offset the visual defect of the bright reflective conductive layer 2. The dark conductive coating can be selected from a black conductive coating, a brown conductive coating, a brown conductive coating, or a dark gray conductive coating; preferably a black conductive paste, such as a carbon paste, etc.; while eliminating the visual effect, the electrical performance of the conductive network can also be improved.
[0082] Please refer to Figure 5 As shown, the present invention also provides a method for preparing a transparent conductive film, comprising the following steps:
[0083] S1 forming a hydrophobic layer 12 on at least one surface of a substrate 11;
[0084] S2: grooves 13 are formed on the surface of the hydrophobic layer 12, and at least some of the grooves 13 are interconnected;
[0085] S3: coating a conductive material in the groove 13 and sintering the material to form a conductive layer 2.
[0086] The materials, thicknesses, etc. of the substrate 1 , the hydrophobic layer 12 , and the conductive layer 2 are set as above and will not be repeated here; the following mainly describes the preparation method steps in detail.
[0087] In step S1 , the present invention adopts a process of blade coating, spin coating, spray coating, slit coating, or inkjet printing to coat the hydrophobic material on the surface of the substrate 11 , and then sinter and cure at 80° C. to 160° C. to obtain the hydrophobic layer 12 .
[0088] The hydrophobic material is selected from at least one or more combinations of nano silicon dioxide, polydimethylsiloxane, or polytetrafluoroethylene.
[0089] In step S2, the present invention forms the groove 13 by laser etching, and the laser power is 1 W to 30 W. The laser etching technology can simplify the groove forming process and reduce the production cost.
[0090] By controlling the laser power or the scanning time / number of scanning times, the groove 13 with the above-mentioned width and depth can be formed.
[0091] The inventors found that the conductive material will shrink during the sintering process. If the conductive material in the wet film state just fills the groove 13, the conductive material shrinks after sintering, and the conductive material in the dry film state cannot fill the entire groove 13, resulting in low conductivity of the entire transparent conductive film 100; if too much conductive material is applied in the wet film state, the conductive material will cover the entire surface of the substrate 1 and cannot form a conductive network in a grid state.
[0092] In step S3 of the present invention, a hydrophilic conductive material is coated in the groove 13 surrounded by the hydrophobic layer 12. By utilizing the hydrophobic properties of the surface of the hydrophobic layer 12, especially in combination with the micro-nano structure of the surface, the affinity of the hydrophobic layer 12 with the conductive material is greatly reduced; therefore, the conductive material is more likely to flow into the groove 13 formed by laser etching during the coating process, rather than forming a continuous film layer on the surface of the hydrophobic layer 12 in the non-groove area. In addition, due to the presence of the groove 13 structure, the conductive material will be affected by capillary action in the groove 13, further promoting the flow and filling of the conductive material into the groove 13. Furthermore, during the coating process, the tension difference between the conductive material and the surface of the hydrophobic layer 12 will also cause the slurry to form a stable distribution state in the groove 13, thereby realizing a precise patterned conductive layer 2. In this way, more conductive material than the volume of the groove 13 can be coated, and the conductive material is only gathered in the groove 13, thereby improving the preparation efficiency and quality of the transparent conductive film 100.
[0093] Specifically, the coating methods of the conductive material include but are not limited to the following two:
[0094] In one embodiment, the conductive material is coated on the entire surface of the substrate 1 , and the conductive material shrinks on the surface into the groove 13 and extends along the groove 13 .
[0095] The coating amount of the conductive material is 1.2 to 3 times the volume of the groove 13 in the wet film state, which can ensure that the entire groove 13 is fully coated with the conductive material, and the conductive material can even be higher than the groove 13. In addition, combined with the effect of the hydrophobic layer 12 in the non-groove area, the conductive material can be concentrated in the groove 13 and bulge upward at the groove 13, and the area extending outside the groove 13 is very small, so there is no need for a scraper, a scraper, a roller, etc. to squeeze and flatten the conductive material, and the conductive material can also be disconnected at the non-groove.
[0096] Alternatively, the coating amount of the conductive material is, in the dry film state, 1 to 1.5 times the volume of the groove 13. The conductive material will fill the entire groove 13 in the width direction, so the height of the conductive layer 2 is usually 1 to 1.5 times the height of the groove 13.
[0097] In another embodiment, the conductive material may be coated only on the groove 13 . Since the non-groove area is made of a hydrophobic material, the conductive material will not overflow and will always remain in the groove 13 .
[0098] The coating amount of the conductive material is set as above to ensure that the entire groove 13 is fully coated with the conductive material, and the conductive material can even be higher than the groove 13; at the same time, it is ensured that the conductive material does not flow outward, thereby forming a partition with the conductive material in the adjacent groove 13.
[0099] In the present invention, the sintering temperature of the conductive material is 80° C. to 160° C. After high-temperature sintering, the conductive material can form a continuous fine-line conductive layer 2 .
[0100] Furthermore, the method for preparing the transparent conductive film further comprises: S4 forming a dark conductive coating on the conductive layer 2 to offset the visual defect of the conductive layer 2 being bright and reflective.
[0101] This step is essentially to blacken the surface of the conductive layer 2. The following methods may be used, but are not limited to: coating a dark conductive coating, vulcanizing the surface of the conductive layer 2, or electroplating the surface of the conductive layer 2 to form a dark conductive coating.
[0102] The transparent conductive film 100 and the preparation method thereof of the present invention will be described in detail below through specific embodiments.
[0103] Comparative example: A groove 13 is directly formed on the substrate 11, and the width of the groove 13 is 10 μm. A nano-silver paste with a thickness of 10 μm is coated on the substrate 11, and then the nano-silver paste outside the groove 13 is removed by scraping. The formed transparent conductive film 100 has a square resistance of ≤1Ω / sq and a transmittance of ≥80%.
[0104] In the comparative example, the surface of the substrate 11 is a hydrophilic surface, so the conductive material cannot exceed the groove 13, otherwise it will diffuse on the surface, affecting the light transmittance, and even causing the conductive materials in two adjacent grooves 13 to contact and conduct. Therefore, the maximum thickness of the wet film conductive film is the depth of the groove 13.
[0105] In Examples 1 to 7, the groove 13 is formed after the hydrophobic layer 12 is formed on the surface of the substrate 11. The surface of the substrate 1 is a hydrophobic layer, and the conductive material shrinks into the groove 13 and does not spread outward. Therefore, the thickness of the wet film conductive film (the thickness of the conductive material in the wet film state) can be greater than the depth of the groove 13.
[0106] Table 1
[0107]
[0108] Example 1 and the comparative example adopt the same coating method, and the thickness of the wet film conductive film is 10 μm, which is the depth of the groove 13, and the square resistance is basically the same as that of the comparative example. This conclusion shows that the square resistance of the transparent conductive film is mainly related to the thickness of the conductive film, and is slightly affected by other factors and can be ignored.
[0109] Embodiments 3 to 4 use different hydrophobic layers to conduct experiments. The hydrophobic layers 12 made of different materials can all make the thickness of the wet film conductive film greater than the depth of the groove 13 of 10 μm, thereby obtaining good sheet resistance.
[0110] Comparing Examples 1 to 3, Example 4 and Example 6, Example 5 and Example 7, it can be seen that in the wet film state, the greater the thickness of the conductive material, the greater the thickness of the conductive layer 2 in the dry film state, and the smaller the square resistance of the transparent conductive film 100. In addition, under the premise of having a hydrophobic layer 12, the conductive layer 2 can protrude from the groove 12 to reduce the square resistance.
[0111] In summary, it can be seen from Examples 1 to 7 and the comparative example that the square resistance of the transparent conductive film 100 obtained by adopting the structure and preparation method of the present invention is better than that of the existing mature solutions, but the influence of the hydrophobic layer 12 on the light transmittance is not very large, which is above 80%.
[0112] The line pitch is the distance between the grooves 13 .
[0113] The transparent conductive film 100 of the present invention can be used as a transparent conductive electrode and applied in back-end products such as antennas, touch electrodes, electromagnetic shielding films, heating films, electronic display devices, solar cells, touch screens, etc.
[0114] In summary, the transparent conductive film 100 of the present invention, by arranging the hydrophobic layer 12 on the surface of the substrate 11, makes the surface of the substrate 1 have a low surface energy, and the conductive material in the area outside the groove 13 is in a water droplet-like state rather than a wet state, and will not spread out, thereby automatically shrinking and finally gathering in the groove 13 to form a conductive grid, and can form a grid-like conductive layer 2 that fills the entire groove 13 or even higher than the groove 13.
[0115] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A transparent conductive film, characterized in that: include: A substrate, the substrate comprising a substrate, a hydrophobic layer located on at least one surface of the substrate, and grooves recessed from the surface of the hydrophobic layer toward the side where the substrate is located, wherein at least some of the grooves are interconnected; The conductive layer is located in the groove.
2. The transparent conductive film according to claim 1, characterized in that: The hydrophobic layer is selected from a combination of at least one or more of a nano-silicon dioxide film layer, a polydimethylsiloxane film layer, or a polytetrafluoroethylene film layer; or The thickness of the hydrophobic layer is 1 μm to 5 μm; or The roughness of the surface of the hydrophobic layer is 1 nm to 200 nm; or The surface contact angle of the hydrophobic layer surface is not less than 90° and not more than 170°.
3. The transparent conductive film according to claim 1, characterized in that: The groove comprises a plurality of interconnected sub-grooves, the plurality of sub-grooves extending in at least two directions; the included angle of the mutually intersecting and interconnected sub-grooves is 40° to 140°; or The groove is in a grid shape as a whole, and the grid pattern is a polygon or an irregular shape, the polygon is a triangle, a quadrilateral, a pentagon, or a hexagon, and the sides of the polygon are straight lines or arcs; or The groove penetrates through the hydrophobic layer; or The groove passes through the hydrophobic layer, and a portion of the groove is recessed inward from the surface of the substrate; or The depth of the groove is 1 μm to 30 μm; or The width of the groove is 3 μm to 20 μm, and the distance between adjacent grooves is 100 μm to 1000 μm.
4. The transparent conductive film according to claim 1, characterized in that: The conductive layer is a conductive network formed by a conductive material coated in the groove, and the conductive layer completely fills the groove; or the conductive layer is higher than the groove in the thickness direction of the substrate.
5. A method for preparing a transparent conductive film, characterized in that: The steps include: forming a hydrophobic layer on at least one surface of a substrate; Grooves are formed on the surface of the hydrophobic layer, and at least some of the grooves are interconnected; A conductive material is coated in the groove and sintered to form a conductive layer.
6. The method for preparing a transparent conductive film according to claim 5, characterized in that: The hydrophobic material is coated on the surface of the substrate by blade coating, spin coating, spray coating, slit coating or inkjet printing, and then sintered and cured at 80° C. to 160° C.; preferably, the hydrophobic material is selected from a combination of at least one or more of nano-silicon dioxide, polydimethylsiloxane, or polytetrafluoroethylene.
7. The method for preparing a transparent conductive film according to claim 5, characterized in that: The groove is formed by laser etching, and the laser power is 1W to 30W.
8. The method for preparing a transparent conductive film according to claim 5, characterized in that: The conductive material is coated on the entire surface of the substrate, and the conductive material shrinks into the groove on the surface and extends along the groove; or Apply the conductive material only in the grooves; The amount of the conductive material in the wet film state is 1.2 to 3 times the volume of the groove; or the amount of the conductive material in the dry film state is 1 to 1.5 times the volume of the groove.
9. The method for preparing a transparent conductive film according to claim 13, characterized in that: The method also includes the step of forming a dark conductive coating on the surface of the conductive layer.
10. Use of a transparent conductive film according to any one of claims 1 to 4 or a transparent conductive film prepared by the preparation method according to any one of claims 6 to 9 in antennas, touch electrodes, electromagnetic shielding films, heating films, electronic display devices, solar cells, and touch screens.
Citation Information
Cited By
Shallow groove type image-text structure, colored three-dimensional image nano printed product and preparation method
CN120356396A
Shallow slot type graphic structure, colored three-dimensional image nano-printed product and preparation method
CN120356396B
